Economic indicators for automobile claim frequencies - Boj, Eva; Castañer, Anna; Claramunt M. Mercè; Costa, Teresa; Roch, Oriol (Estudios de Economía, 2019)
This article examines the relationship between observed claim frequencies in the automobile insurance line and the evolution of selected economic magnitudes. From a variety of economic variables, we aim to identify the main factors affecting claim frequencies, while controlling for other legislative and demographic factors. Through a dynamic regression model, the analysis is conducted for three different categories of vehicles and for a variety of coverages. A comprehensive dataset from the main Spanish insurance companies is used to calibrate the model. The evidence might assist companies to improve ratemaking.